Efficacy and safety of cumaru syrup as complementary therapy in mild persistent asthma: a double-blind, randomized, placebo-controlled study - Elisete Mendes Carvalho; Gilmara Holanda da Cunha; Francisco Vagnaldo Fechine; Célia Regina Amaral Uchôa; Manoel Odorico de Moraes Filho; Fernando Antônio Frota Bezerra; Maria Elisabete Amaral de Moraes (Universidade de São Paulo, 2012)
Amburana cearensis is a medicinal plant known as "cumaru". It is used in Northeast Brazil in the treatment of respiratory diseases. This was a randomized, double-blind, placebo-controlled study, with the aim of evaluating the efficacy and safety of cumaru syrup as complementary therapy in mild persistent asthma. The study consisted of 3 phases, pre-treatment, treatment and post-treatment. The primary efficacy outcome was comparison of the changes reported by patients of the cumaru and placebo groups after treatment, using the "Asthma Quality of Life Questionnaire" (AQLQ). The secondary outcome was the effect of cumaru syrup on lung function based on spirometry. The results showed that in the cumaru group, the proportion of patients who had global improvement in asthma symptoms was significantly greater (61.90%, P=0.0009) than in the placebo group (9.52%). Only the spirometric parameters Forced Vital Capacity (FVC) and Forced Expiratory Volume in 1 second (FEV1) showed significant intergroup differences in post-treatment (P<0.05). The hematological and serum chemistry tests performed in the pre-treatment and post-treatment showed no statistically significant differences (P>0.05). Adverse events were reported by 3 patients (14.29%) in the cumaru group and 3 patients (14.29%) in the placebo group. All adverse events were considered non-serious and mild. Amburana cearensis é uma planta medicinal conhecida como "cumaru". No Nordeste do Brasil é usada no tratamento de doenças respiratórias. Este é um estudo randomizado, duplo-cego e controlado por placebo, com o objetivo de avaliar a eficácia e segurança do xarope de cumaru como terapia complementar da asma persistente leve. O estudo consistiu de três fases, pré-tratamento, tratamento e pós-tratamento. A variável primária para determinação da eficácia foi a comparação das mudanças referidas pelos pacientes dos grupos cumaru e placebo após o tratamento, usando o "Questionário sobre Qualidade de Vida na Asma" (QQVA). A variável secundária foi o efeito do xarope de cumaru na função pulmonar baseado na espirometria. Os resultados mostraram que no grupo cumaru, a proporção de pacientes com melhora global dos sintomas da asma foi significativamente maior (61,90%, P=0.0009) que no grupo placebo (9,52%). Somente os parâmetros espirométricos, capacidade vital forçada (CVF) e volume expiratório forçado no primeiro segundo (VEF1), mostraram diferença intergrupo significtivas no pós-tratamento (P<0.05). Os testes hematológicos e do soro realizados no pré-tratamento e pós-tratamento não mostraram diferenças estatisticamente significativas (P>0.05). Eventos adversos foram reportados por 3 pacientes (14,29%) no grupo cumaru e 3 (14,29%) no grupo placebo. Todos os eventos adversos foram não sérios e leves.